A Simple Approach to Enhance Multiprobe Soil Cone Penetrometer Analyses. Issue 6 (3rd November 2016) - Balkcom, Kipling S.; Duzy, Leah M.; Mitchell, Charles C.; Delaney, Dennis P.
Abstract : Core Ideas: We describe a method to quantify soil strength with a multiprobe cone penetrometer. An area‐under‐the‐curve calculation compares soil strength across treatments. This value simplifies comparisons for depths and row positions of the soil profile. Soil penetrometers measure penetration resistance to characterize soil strength for different management practices, primarily tillage. Our objective was to demonstrate a simple approach to quantify soil strength differences among treatments collected with a multiprobe cone penetrometer using cone index measurements to complement contour graphs and statistical analyses. The approach involves obtaining average cone index values by row position and calculating the area under the curve for cone index (AUCC.I. ), with units of megapascal‐centimeters (MPa‐cm). Data were collected from a tillage and cover crop experiment in Prattville, AL (November 2009), and at the Old Rotation experiment in Auburn, AL (December 2014). Cone index values were averaged across depths for five row positions perpendicular to the center of the row (0 cm) and 22.5 and 45 cm on either side of the crop row. The approach identified that three conservation tillage implements reduced penetration resistance compared with no tillage based on AUCC.I. values from the Prattville experiment. Although no statistical comparisons were possible from the unreplicated Old Rotation experiment, AUCC.I. values were numerically lower for the 3‐yr rotation compared with continuous cotton ( Gossypium hirsutum L.) and the 2‐yr rotation. Results from both sets of cone index measurements demonstrated that the area under the curve (AUC) approach can be used to quantitatively distinguish among treatments. Results from the AUC approach can be used to facilitate simple comparisons among treatments in field experiments and aid in the interpretation of traditional statistical analyses combined with contour graphs.